A lowland story: behaviour and phenotypic integration in a cline between two incipient species of neotropical dart-poison frogs (2021)
In the animal world there are many strategies to avoid predation. One of them is colouring as a form of protection, either with aposematism or crypsis. These are subject to different pressures such as natural selection, sexual selection and different intra- and interspecific communications, which will be key to speciation events. In these events, it is expected that colouration, being subject to different pressures, will correlate with behaviour because conspicuous individuals are expected to have more active behaviours than cryptic ones. This behavioural variation may influence the ability to display optimal behaviour in different environments, affecting survival and reproductive success. In this study we used individuals from a colour cline between the species P. bicolor and P. aurotaenia described by different authors. With this in mind, the question arose whether there is a correlation between colour behaviour and body size. For this we made comparisons between anxious and exploratory behaviour using EthoVision and comparisons between body size and colour using SpectraSuite analysed with Pavo and ImageJ. We found differences in colouring in the dorsal lines of the three populations where there appears to be a continuous pattern, but we found no pattern in ventral colouring in this cline. Likewise, we found a behavioural pattern in anxiety, but not in exploration. In addition, we found no correlation between these behavioural aspects and aspects of colouration and body size.